Death waits in the dark - Buckley, Julia, 1964- (Buckley, Julia, 1964- Writer's apprentice mysteries., 2019)
It's summertime, and Lena and Camilla are busy working away while a town vandal runs amok. Things get even more complicated when Jane Wyland pays Camilla a not-so-friendly visit and gives her an ultimatum: reveal Camilla's husband James's family secret, or she will. Lena assures Camilla that nothing will come of the woman's threats, since the family has no secrets to hide. When Jane Wyland is later found dead, they're convinced that whatever secret she was planning to expose led to her death. With Lena's assistance, Camilla is determined to solve the case before the finger points at her...